Low Sugar Is Not Always Good: Impact of Specific O-Glycan Defects on Tip Growth in Arabidopsis. Issue 3 (5th May 2015) - Velasquez, Silvia M.; Marzol, Eliana; Borassi, Cecilia; Pol-Fachin, Laercio; Ricardi, Martiniano M.; Mangano, Silvina; Juarez, Silvina Paola Denita; Salter, Juan D. Salgado; Dorosz, Javier Gloazzo; Marcus, Susan E.; Knox, J. Paul; Dinneny, Jose R.; et al.
Abstract : Mutants of the O-glycosylation pathway of extensins as well as molecular dynamics simulations uncover the effects of the O-glycosylation machinery on root hair tip growth.